Inflammatory Th17 cells are correlated with insulin resistance and erythrocyte parameters in overweight and obese children - Artemniak-Wojtowicz, Dorota; Rumińska, Małgorzata; Stelmaszczyk-Emmel, Anna; Paluchowska, Monika; Pyrżak, Beata Ewa; Kucharska, Anna Małgorzata (Frontiers in Endocrinology, 2024)
Introduction: Obesity is thought to be accompanied by chronic, low-grade, inflammation. The adipocytes are present in the subcutaneous and visceral fat tissue and contribute to bone marrow cells compartment. Therefore, it poses a question whether the factors influencing adipocyte functions also have an impact on the hematopoietic function of the bone marrow. The aim of our study was to evaluate the association between erythrocyte parameters, the proinflammatory Th17 lymphocytes and IR markers in children with excessive body weight. Methods: 27 overweight/obese and 15 normal-weight children aged 8–18 years were enrolled in the study. The analysis included anthropometric measurements, evaluation of Th17 cells frequency, erythrocyte parameters, and carbohydrate metabolism parameters. Results: In overweight/obese children there were higher erythrocyte count (p = 0.00002), haemoglobin (HGB) concentration (p = 0.005) and frequency of Th17 cell (p = 0.048). Anthropometric parameters correlated with erythrocyte parameters, as well as Th17 cell frequency in all children. The erythrocyte count correlated with the Th17 subset (p = 0.01, r = 0.38). Moreover, in all children was found the correlation between erythrocyte and fasting insulin (FI) (p = 0.00005, r = 0.58), HOMA-IR (p = 0.00005, r = 0.58), QUICKI (p = 0.000042, r = -0.59), as well as between HGB and FI (p = 0.037, r = 0.32), HOMA-IR (p =0.37, r = 0.32), and QUICKI (p = 0.049, r = -0.31). In the overweight/obese group, erythrocyte count correlated with insulin 2 h after OGTT (p = 0.04, r = 0.4), while HGB correlated with glucose and insulin 2 h after OGTT (p = 0.018, r = 0.45; p = 0.04, r = 0.44, respectively). Conclusions: Our study confirmed that the erythrocyte parameters are higher in children with obesity and are positively correlated with insulin resistance and proinflammatory Th17 lymphocyte. Thus, it can be concluded that erythrocyte parameters reflect the risk of developing IR in response to chronic inflammation associated with obesity. These are simple, easily accessible and repeatable tests that, in the assessment of obese patients, may herald the developing metabolic syndrome and serve as a helpful additional tool for assessing the effectiveness of treatment.